2009
DOI: 10.1177/1321103x09103629
|View full text |Cite
|
Sign up to set email alerts
|

Naturally emerging self-regulated practice behaviors among highly successful beginning recorder students

Abstract: A B S T R A C T The purpose of this research study was to extend current scholarship on self-regulated practice behaviors of young instrumentalists to the general music recorder classroom. This qualitative study explored the reflections of successful beginning recorder players in relation to the self-regulated practice model. Interviews were conducted with three high-achieving third-grade recorder players and responses were coded for themes relating to self-regulated practice. Results support the notion that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…47–48). In this study (Bartolome, 2009), the recorder students were not explicitly instructed in learning strategies, and spontaneously developed a self-regulated attitude; however, the importance of social support (namely, from the parents) in organizing and managing these students’ musical practice was reported and highlighted. In general, students gradually develop autonomous skills for organizing, regulating, and monitoring their learning activity (McPherson and Zimmerman, 2011).…”
Section: Metacognition and Self-regulated Learning In Music Performancementioning
confidence: 85%
See 1 more Smart Citation
“…47–48). In this study (Bartolome, 2009), the recorder students were not explicitly instructed in learning strategies, and spontaneously developed a self-regulated attitude; however, the importance of social support (namely, from the parents) in organizing and managing these students’ musical practice was reported and highlighted. In general, students gradually develop autonomous skills for organizing, regulating, and monitoring their learning activity (McPherson and Zimmerman, 2011).…”
Section: Metacognition and Self-regulated Learning In Music Performancementioning
confidence: 85%
“…As they gain expertise in music learning, music students develop a self-regulated approach to musical practice, showing a wider range of learning strategies, and increasingly effective ways of selecting and applying them during individual practice. Bartolome (2009) found that young beginner recorder players who experienced positive results in performance showed a high level of metacognitive competence that resulted in self-regulated practice. They had a goal-oriented approach to musical practice, and they effectively used a large set of learning strategies to study the musical pieces they were assigned during music lessons.…”
Section: Metacognition and Self-regulated Learning In Music Performancementioning
confidence: 99%
“…SRL is a feature of deliberate practice (Bartolome 2009;McPherson and Renwick 2011;Miksza 2007), and SRL is widely recognised as a core aspect of metacognition (McPherson and Zimmerman 2011;Zimmerman and Schunk 2011). SRL research has been conducted in four broad domains: (1) metacognitive and cognitive; (2) social and motivational; (3) behavioural and cognitive; and (4) developmental (Zimmerman and Schunk 2011).…”
Section: Self-regulated Learning and Transactional Regulationmentioning
confidence: 99%
“…For music educators, self-regulation indicators disclose insights about values attributed to musical improvement and to strategies used during learning activities (Bartolome 2009;Ginsborg et al 2009;Hallam 2001;Leon-Guerrero 2008;McCormick and McPherson 2003;McPherson and McCormick 1999;McPherson and McCormick 2006;Nielsen 2001).…”
Section: Introductionmentioning
confidence: 99%